2013
DOI: 10.1186/1471-2172-14-24
|View full text |Cite
|
Sign up to set email alerts
|

Proton channel HVCN1 is required for effector functions of mouse eosinophils

Abstract: BackgroundProton currents are required for optimal respiratory burst in phagocytes. Recently, HVCN1 was identified as the molecule required for the voltage-gated proton channel activity associated with the respiratory burst in neutrophils. Although there are similarities between eosinophils and neutrophils regarding their mechanism for respiratory burst, the role of proton channels in eosinophil functions has not been fully understood.ResultsIn the present study, we first identified the expression of the proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 51 publications
2
46
0
Order By: Relevance
“…Consequently, neutrophils lacking Hv1 channel displayed a diminished ability to migrate in vitro in response to the chemoattractant N-formyl-Met-Ile-Val-Ile-Leu bacterial peptide (El Chemaly et al, 2010). Afterward, Zhu et al (2013) corroborated these findings in an in vivo model of peritonitis induced by intraperitoneal injection of thioglycollate. In this experimental setting, the number of neutrophils infiltrating the peritoneal cavity was reduced twofold in Hv1-deficient mice compared with wild-type littermates, indicating that Hv1 channel regulates neutrophils migration toward the sites of inflammation in vivo (Zhu et al, 2013).…”
Section: Role Of Proton Channel Hv1 In Immune Cellsmentioning
confidence: 62%
See 2 more Smart Citations
“…Consequently, neutrophils lacking Hv1 channel displayed a diminished ability to migrate in vitro in response to the chemoattractant N-formyl-Met-Ile-Val-Ile-Leu bacterial peptide (El Chemaly et al, 2010). Afterward, Zhu et al (2013) corroborated these findings in an in vivo model of peritonitis induced by intraperitoneal injection of thioglycollate. In this experimental setting, the number of neutrophils infiltrating the peritoneal cavity was reduced twofold in Hv1-deficient mice compared with wild-type littermates, indicating that Hv1 channel regulates neutrophils migration toward the sites of inflammation in vivo (Zhu et al, 2013).…”
Section: Role Of Proton Channel Hv1 In Immune Cellsmentioning
confidence: 62%
“…Supporting this idea though, Kasahara et al (2016) showed that neutrophils lacking GM-CSF receptor signaling had reduced NOX activity, and consequently, their ability to kill Aspergillus fumigatus during respiratory burst was impaired, suggesting that a GM-CSFmediated mechanism of Hv1/NOX regulation could apply likewise in neutrophils. Hv1 also has an important role in the migration of neutrophils toward the sites of inflammation (El Chemaly et al, 2010;Zhu et al, 2013). This function of Hv1 controlling neutrophil migration might very well apply in the context of the TME, because it is a site of inflammation where many cytokines (TNF-a, IFN-g) and chemokines (CXCL2, CXCL1, CCL3, CXCL6) are released to attract neutrophils (Fridlender and Albelda, 2012) (Fig.…”
Section: Role Of Proton Channel Hv1 In Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing evidence shows that there is an important link between hypoxia and eosinophil function [19]; hypoxic stress induces the transcription of several factors, like the hypoxia inducible factor (HIF-1), responsible for oxygen homeostasis [20,21], and changes in eosinophil cellular profile enhancing its ability to migrate thru blood vessels, decreasing cellular apoptosis, and prolonging its half-life [19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…energy landscape | kinetic model | global fit M embrane proteins controlled by the membrane potential are ubiquitous among phyla and are involved in a variety of fundamental biological tasks such as action potential generation and propagation, pacemaker activity, insulin secretion, G proteins and lipid signaling, innate immunity, and cell homeostasis (1)(2)(3)(4)(5)(6)(7)(8). In most of these proteins, voltage sensitivity is conferred by small structural modules called voltage sensor domains (VSDs) that encompass four transmembrane helices S1-S4 (9).…”
mentioning
confidence: 99%